2015
DOI: 10.1051/0004-6361/201425003
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between heartbeat oscillations and wind outflow in microquasar IGR J17091-3624

Abstract: Aims. During the bright outburst in 2011, the black hole candidate IGR J17091-3624 exhibited strong quasi-periodic flare-like events (on timescales of tens of seconds) in some characteristic states, the so-called heartbeat state. From the theoretical point of view, these oscillations may be modeled by the process of accretion disk instability, driven by the dominant radiation pressure and enhanced heating of the plasma. Although the mean accretion rate in this source is probably below the Eddington limit, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 43 publications
10
45
2
Order By: Relevance
“…The observed behaviour of the disk will then be characterized by the deterministic chaos. The recent hydrodynamical simulations of the global accretion disk evolution confirm that the quasi-periodic flare-like events observed in couple sources, are in a good quantitative agreement with the radiation pressure instability model (Janiuk et al, 2015). At least eight of the known BH X-ray binaries should have their Eddington accretion rates large enough for the radiation pressure instability to develop.…”
Section: Discussionsupporting
confidence: 65%
“…The observed behaviour of the disk will then be characterized by the deterministic chaos. The recent hydrodynamical simulations of the global accretion disk evolution confirm that the quasi-periodic flare-like events observed in couple sources, are in a good quantitative agreement with the radiation pressure instability model (Janiuk et al, 2015). At least eight of the known BH X-ray binaries should have their Eddington accretion rates large enough for the radiation pressure instability to develop.…”
Section: Discussionsupporting
confidence: 65%
“…One of the best studied examples is the microquasar GRS 1915+105, which in some spectral states exhibits cyclic flares of its X-ray luminosity, well fitted to the limit cycle oscillations of an accretion disk on timescales of tens or hundreds of seconds Taam et al (1997); Belloni et al (2000); Neilsen et al (2011). Those heartbeat states are known since 1997, when the first XTE PCA observations of this source were published (Taam et al 1997), while recently yet another microquasar of that type, IGR J17091-3624, was discovered (Revnivtsev et al 2003;Kuulkers et al 2003;Capitanio et al 2009); heartbeat states were also found for this source (Altamirano et al 2011b;Capitanio et al 2012;Pahari et al 2014;Janiuk et al 2015). Furthermore, a sample of sources proposed in Janiuk & Czerny (2011) suggested to undergo luminosity oscillations, possibly induced by the non-linear dynamics of the emitting gas.…”
Section: Introductionmentioning
confidence: 78%
“…We are solving the time-dependent vertically averaged disk equations with radiation pressure in the Newtonian approximation, following the methods described in Janiuk et al (2002), and subsequent papers (Janiuk & Czerny 2005;Czerny et al 2009;Janiuk et al 2015). The disk is rotating around the central object with mass M with Keplerian angular velocity Ω = GM r 3 , and maintains the local hydrostatic equilibrium in the vertical direction P = C 3 ΣΩ 2 H. The latter gives the necessary relationship between pressure P, angular velocity Ω, and disk vertical thickness H. C 3 is the correction factor regarding the vertical structure of the disk.…”
Section: Equationsmentioning
confidence: 99%
“…It suggests that the radiationpressure instability may only clearly appear when the accretion rate is close to the Eddington rate. The magnetic field, wind and corona can stabilize the disk and suppress the oscillations, or at least make them less pronounced (Czerny et al 2003;Zheng et al 2011;Janiuk et al 2015;Sadowski 2016), which will lead to a much higher critical value of the Eddington rate than that of the pure disk. Since the strength of those stabilizing mechanisms is difficult to estimate, the observational approach to the presence or absence of the radiation pressure instability has a clear advantage.…”
Section: The Universal Correlation Between Bolometric Luminosity and mentioning
confidence: 99%